Children’s multisensory experiences in museums: how olfaction interacts with color - Kucirkova, Natalia I.; Speed, Laura J. (Frontiers in Education, 2023)
This case study was designed to engage children's sense of smell through a story-related museum exhibition. Children's responses to the exhibition, with particular attention to their olfactory perceptions of the odours at the exhibition, were solicited through researcher-child interviews and children's drawings. Responses from 28 children (girls N=14, boys N=14) aged between 4.5-8 years were analysed after they visited the exhibition using the crossmodal association and multisensory theories. Interview data showed that dark (brown and black) colours elicited children's negative olfactory associations for both positive and negative odours. Children's drawings did not seem to make references to the odours at the exhibitions but rather their preferences for the different story characters. We theorise about the associations between smell and colours in children's responses and distil some key learnings for multisensory museology.